2015
DOI: 10.1007/s12264-014-1524-2
|View full text |Cite
|
Sign up to set email alerts
|

Early hypoactivity of hippocampal rhythms during epileptogenesis after prolonged febrile seizures in freely-moving rats

Abstract: Prospective and experimental studies have shown that individuals with early-life complex/prolonged febrile seizures (FSs) have a high incidence of temporal lobe epilepsy during adulthood, revealing a close relationship between FSs and epilepsy. However, little is known about how epileptogenesis develops after FSs. The present study was designed to investigate acquired seizure susceptibility and analyze local field potentials during the latent period after FSs. We found that the seizure susceptibility decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Using whole-cell patch clamp, similar alterations were seen in cultured rat cortical neurons subjected to hyperthermia (Wang et al 2011). Increased inhibitory pre-synaptic terminals were identified in CA3 neurons of P35 rats that were exposed to a prolonged FS paradigm at P8 (Feng et al 2015). Our data showing decreased AP threshold in WT and RH/+ neurons following A/PFE are consistent with these prior results.…”
Section: Discussionmentioning
confidence: 99%
“…Using whole-cell patch clamp, similar alterations were seen in cultured rat cortical neurons subjected to hyperthermia (Wang et al 2011). Increased inhibitory pre-synaptic terminals were identified in CA3 neurons of P35 rats that were exposed to a prolonged FS paradigm at P8 (Feng et al 2015). Our data showing decreased AP threshold in WT and RH/+ neurons following A/PFE are consistent with these prior results.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β concentration increases transiently after infantile FS, while the subsequent epileptogenesis is a long-term and dynamic process 31 32 . How does this transient change of IL-1β modify neuronal excitability in a long-term process?…”
Section: Discussionmentioning
confidence: 99%
“…Schuchmann et al [19] developed another animal model using a warm chamber as the heat source to raise the body temperature to an appropriate level. In our study, we chose the latter because we found that the warm chamber has lower mortality and fewer burns than heated air [38,40,64,65]. Besides, Dube et al [14] and Gassen et al [66] used mouse FS models, facilitating the use of genetically mutant mice and other specific techniques.…”
Section: Experimental Febrile Seizure Modelsmentioning
confidence: 99%